Development of Project-Based Learning and Gallery Learning Methods to Improve Social Competence and Creative Thinking in Elementary School Students in the Era of the New Normal - Suhartono Suhartono (UM Purwokerto Press, 2025)
This study aims to develop a hybrid learning model (combining offline and online components) based on project-based learning (PjBL) using the gallery learning method to enhance the social and creative thinking competencies of elementary school students in adapting to the new normal. The model was developed through the stages of problem identification, development design, testing, and product evaluation. This learning approach requires students to develop collaboration and reflection skills, helping them improve their social skills. To date, the implementation of PjBL has primarily been conducted through direct learning, with academic achievement as the primary focus of the study. Meanwhile, social competencies are closely related to intercultural skills, language skills, communication skills, networking skills, teamwork skills, compromise and cooperation skills, knowledge transfer skills, and leadership skills. Personalities related to tolerating ambiguity, seeking identification, overcoming obstacles, pursuing self-growth, internal motivation, and choosing adventure need to be cultivated. Both of these competencies are easier to develop in face-to-face learning than in online learning, although adjustments must be made to the situation and conditions at each school. These skills are still inadequate at the elementary school level, which affects the lack of development of project-based learning. In this study, the research subjects involved 226 students and 23 classroom teachers. Data collection was conducted using interview sheets, tests, and questionnaires. Quantitative data analysis techniques included parametric statistical tests for average achievement using SPSS one-sample t-tests, Z-tests for proportions, paired-sample t-tests for mean differences, and N-gain tests. The results of the study indicate that (1) the developed learning tools are suitable for use, namely the syllabus with a score of 40 out of a maximum of 40 (valid), the lesson plan with a score of 60 out of a maximum of 60 (valid), the teaching materials with a score of 54 out of a maximum of 56 (valid), and the questions with a score of 38 out of a maximum of 40 (valid). (2) The project-based learning tools integrated with the gallery learning method can enhance students' social competencies and creative thinking skills. (3) Teacher feedback received a score of 97 out of a maximum of 100, indicating an excellent response. The use of project-based learning materials integrated with the gallery learning method to enhance social competencies and creative thinking skills in students adapted to the new normal era, represents an innovation in elementary school education.